2005
DOI: 10.3200/jach.53.4.167-174
|View full text |Cite
|
Sign up to set email alerts
|

Illicit Use of Prescribed Stimulant Medication Among College Students

Abstract: The authors investigated illicit use of stimulant medications at a midwestern university. They used a questionnaire to (a) examine the extent to which university students illicitly used stimulant medications prescribed for attention-deficit hyperactivity disorder; (b) determine why college students abused such drugs; and (c) identify the factors that predicted illicit use of prescribed stimulant medication. Findings revealed that 17% of 179 surveyed men and 11% of 202 women reported illicit use of prescribed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
153
4
7

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(182 citation statements)
references
References 12 publications
16
153
4
7
Order By: Relevance
“…We also found that most students nonmedically use stimulants "purposefully" as an academic aid, that is, to help them study or cram for exams and write papers. 11, 31 We also found that the overwhelming majority of college students obtain prescription stimulants from friends, who either have or do not have a legitimate prescription.13 , 33 Lastly, consistent with McCabe et al, 32 we find it noteworthy that the students taking prescribed ADHD medication were outnumbered by lifetime nonmedical users of prescription stimulants, at a ratio of nearly five to one (45 vs. 218).…”
Section: Nih-pa Author Manuscriptsupporting
confidence: 76%
See 2 more Smart Citations
“…We also found that most students nonmedically use stimulants "purposefully" as an academic aid, that is, to help them study or cram for exams and write papers. 11, 31 We also found that the overwhelming majority of college students obtain prescription stimulants from friends, who either have or do not have a legitimate prescription.13 , 33 Lastly, consistent with McCabe et al, 32 we find it noteworthy that the students taking prescribed ADHD medication were outnumbered by lifetime nonmedical users of prescription stimulants, at a ratio of nearly five to one (45 vs. 218).…”
Section: Nih-pa Author Manuscriptsupporting
confidence: 76%
“…From a methodological standpoint, researchers should arrive at a consensus regarding terminology, rather than continuing to use a variety of terms, such as "misuse," 13,33 "abuse," 40 "illicit use," 12,31 and "unsanctioned use." 41 In our estimation, NPS is a difficult behavior to assess due to the high variability in how participants subjectively interpret the wording of questionnaire items, and these difficulties are compounded with populations being treated for ADHD.…”
Section: Research Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 Although diverted STIMs must ultimately have come from someone, the current data do not assess whether the patients who filled their prescriptions are the same people who are using or selling their medication. Future research would be needed to examine the supply side of diversion to understand to what degree prescriptions that are intended for insured persons in this age group end up in the hands of others.…”
Section: ■■ Discussionmentioning
confidence: 97%
“…In previous studies, discrepant results were reported about rates of MPH use among genders [16][17][18] . In the Monitoring to Future Study, it was reported that MPH misuse within the prior year is more common among males than females 19 .…”
Section: Discussionmentioning
confidence: 80%